Surgical correction of breast animation deformity with implant pocket conversion to a prepectoral plane - Holland, Michael C; Lentz, Rachel; Sbitany, Hani (Plastic and reconstructive surgery (1963), 2020)
Animation deformity is an undesirable outcome of subpectoral breast reconstruction that results in abnormal breast contraction with activity, breast pain, and increased implant visibility. Surgical correction requires implant removal and conversion of the reconstruction to a prepectoral plane. We present our institutional experience with our preferred surgical technique to treat this challenging problem, and outline solutions for increased success in these patients. A retrospective review was performed of all patients undergoing conversion of their subpectoral breast reconstruction to a prepectoral plane at our institution. Patient demographics and surgical details were analyzed, and post-operative outcomes and morbidity were assessed. The effects of changing operative strategies on enhanced success are also reported. A total of 80 breast conversions were performed over a 2.5 year period. All patients demonstrated resolution of animation deformity on mean follow up of 15.2 months. Two reconstructions (2.5%) required an unplanned return to operating room, while 11 reconstructions (13.8%) were treated for infection. Pre-conversion fat grafting and the utilization of acellular dermal matrix (ADM) were both associated with reduced incidence of post-operative asymmetry and capsular contracture (p < 0.05). There were no reconstructive failures associated with conversion to a prepectoral pocket. Treatment of animation deformity in the reconstructed patient can be safely performed by surgical conversion to a prepectoral plane. The use of ADM, and pre-conversion fat grafting, in appropriate patients can improve results. We promote this operative algorithm for all reconstructive patients experiencing symptomatic animation deformity with subpectoral breast reconstruction.